Hydrothermal synthesis of K-OMS 2 and its application on the thermal catalytic oxidation of toluene and benzene - Millanar, Jessa Marie J. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Toluene and benzene are hazardous air pollutants commonly found in the atmosphere at relatively high concentrations. Due to its known toxicity, numerous studies have been performed to remove these compounds. In this study, octahedral molecular sieve type of manganese oxide (OMS-2) synthesized via the uncalcined route was used to thermally decompose toluene and benzene. Central composite design (CCD) was used to determine the effects of hydrothermal time and hydrothermal temperature. Hydrothermal time and hydrothermal temperature were found to have significant main and interaction effects on toluene removal. In line with this, lower hydrothermal temperature and time improve OMS-2 crystallinity and thus toluene removal. Scanning electron micrograph (SEM) images and x-ray diffractometer (XRD) patterns confirmed the formation of OSM-2. The performance of the optimized OMS-2 for toluene and benzene decomposition at various gas hourly space velocity (GHSV) and reaction temperature was also investigated in this study. GHSV and reaction temperature have significant main effects on toluene and benzene removal. In general, toluene and benzene removal increase with increase in GHSV and reaction temperature. Toluene and benzene removal of about 100% and 62% respectively were obtained at GHSV of 120, 000/hr and reaction temperature of 250°C. The study was successfully synthesized through the hydrothermal uncalcined route and the OMS-2 obtained has excellent efficiency on toluene and benzene removal.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Air -- Purification -- Photocatalysis; Toluene; Benzene